Ninth European Powder Diffraction Conference : Prague, September 2-5, 2004 (De Gruyter Oldenbourg, 2006)
Zeitschrift für Kristallographie. Supplement Volume 23 presents the complete Proceedings of all contributions to the IX European Powder Diffraction Conference in Prague 2004: Method Development and Application Instrumental Software Development Materials Supplement Series of Zeitschrift für Kristallographie publishes Proceedings and Abstracts of international conferences on the interdisciplinary field of crystallography.